Saudi Bachelor Nursing Students' Perceptions of Academic Advising: Descriptive Quantitative Study - Jumah, Jawaher Abdullah Bin; Nouh, Nazirah Omar; Faltah, Reemah; Alonazi, Maha (South Eastern European Journal of Public Health, 2024)
Academic advising is identified as a progression to assist the students in determining their competencies which would guide them to find and develop their academic identity and ensure which study program and major would fit their capabilities within the facilitated opportunities. Aim This descriptive quantitative research was to analyze the relationship between undergraduate students and their academic advisors, evaluate the obstacles of the academic advising process from their' perception, and assess the resolutions of the academic advising. Methods: This descriptive quantitative study was conducted on a convenience sample of 200 nursing students in different courses and levels in the College of Nursing at King Saud University using demographically collected data. ResultsThere was a significant indication of a relationship between social demographic data and student perception of academic advising. Conclusions Implementing academic advisory could improve the students' achievements and overcome learning obstacles that could affect nursing students' learning outcomes. Suitable supervision from academic affairs strengthens their positions.